Giardia agilis: Ultrastructure of the Trophozoites in the Frog Intestine - Sogayar, Maria Inês L; Gregório, Elisa Aparecida [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1998)
Intestine samples of Bufo sp. tadpoles with parasitism confirmed for Giardia agilis were studied by transmission electron microscopy. The G. agilis trophozoites were long and thin. The plasma membrane was sometimes undulated and the cytoplasm, adjacent to the dorsal and ventral regions, showed numerous vacuoles. The two nuclei presented prominent nucleoli. The cytoplasm was electron-dense with free ribosomes, glycogen and rough endoplasmic reticulum-like structures. Polyhedral inclusions were observed in the cytoplasm and outside the protozoan; some of these inclusions exhibited membrane disruption. The flagella ultrastructure is typical, with the caudal pair accompanied by the funis. Next to the anterior pair, osmiophilic material was noticed. The ventro-lateral flange was short and thick, supported by the marginal plates that penetrated into its distal extremity; only its distal portion had adjacent osmiophilic filament. The G. agilis trophozoites showed the general subcellular feature of the genus. However, the ventro-lateral flange ultrastructure was an intermediate type between G. muris and G. duodenalis.
Keywords: ultrastructure; Giardia agilis; trophozoite